Geomorphology, growth pattern and substrates of the inshore Kimberley Reefs, Western Australia: A spatial analysis approach - Kordi, Moataz Nael S (Curtin University, 2016)
Coral reefs occur extensively along the northwest coast of Australia forming major geomorphic features of the Kimberley coast. These reefs are seldom studied due to limited accessibility and extreme water conditions, which make management of these vital ecosystems a challenging task. Remote sensing and GIS were used in this study to create a foundation for the first comprehensive geodatabase of theses reefs and to provide some of the first detailed analysis ofreef distribution.